1998
DOI: 10.1212/wnl.50.4.972
|View full text |Cite
|
Sign up to set email alerts
|

White matter changes with normal aging

Abstract: We evaluated brain tissue compartments in 72 healthy volunteers between the ages of 18 and 81 years with quantitative MRI. The intracranial fraction of white matter was significantly lower in the age categories above 59 years. The CSF fraction increased significantly with age, consistent with previous reports. The intracranial percentage of gray matter decreased somewhat with age, but there was no significant difference between the youngest subjects and the subjects above 59. A covariance adjustment for the vo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

27
254
3
2

Year Published

1999
1999
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 414 publications
(286 citation statements)
references
References 41 publications
27
254
3
2
Order By: Relevance
“…In some studies, such as our previous study, white matter volume did not appear to change with age [2,19,33]. However, results of some recent studies suggest that significant white matter volume loss does occur, at least in some cerebral regions [15,34,36]. The present study extends our earlier work by: examining a larger age range; providing detailed volumetric characterization of multiple subcortical and limbic structures; providing lobar measures of cortical gray matter, underlying white matter, and signal abnormalities; providing measures of cerebellar gray and white matter; and applying statistical techniques for comparing the age-effects in different regions.…”
Section: Introductionmentioning
confidence: 52%
See 1 more Smart Citation
“…In some studies, such as our previous study, white matter volume did not appear to change with age [2,19,33]. However, results of some recent studies suggest that significant white matter volume loss does occur, at least in some cerebral regions [15,34,36]. The present study extends our earlier work by: examining a larger age range; providing detailed volumetric characterization of multiple subcortical and limbic structures; providing lobar measures of cortical gray matter, underlying white matter, and signal abnormalities; providing measures of cerebellar gray and white matter; and applying statistical techniques for comparing the age-effects in different regions.…”
Section: Introductionmentioning
confidence: 52%
“…These have confirmed volume decreases in cortical gray matter [2,31,33,34,39], cerebral hemispheres [7,8], and basal ganglia structures [27,30,35], and increases in volumes of [15,28], or odds of [8], signal hyperintensities in the white matter. In some studies, such as our previous study, white matter volume did not appear to change with age [2,19,33].…”
Section: Introductionmentioning
confidence: 52%
“…25,26 Cortical cholinergic nerve fibers showing age-related changes 27 have been found in the cerebral cortex, suggesting that atrophy of the white matter may be due to a decrease in the number of nerve fibers. Nusbaum et al suggest that there is data to indicate that a more diffuse process in white matter may be taking place that is not necessarily confined to regions of abnormal signal intensity on conventional MR images.…”
Section: Dti and Agingmentioning
confidence: 99%
“…The boundaries between normal age-related cognitive changes and the very earliest signs ofAD may be particularly difficult to delineate in the Very-Old, primarily because many of the early structural and functional changes of AD overlap with changes observed either in normal aging or in the context of other disease processes. A number of studies have shown that normal aging is associated with mild brain atrophy on structural magnetic resonance (MR) imaging (Jack et al, 1998a(Jack et al, , 1999Jernigan et al, 2001;Pfefferbaum et al, 1994), decreased hemodynamic response on functional MR imaging (D'Esposito et al, 1999), reduced synaptic density (Masliah et al, 1993), increased white matter abnormalities (Guttman et al, 1998;Jernigan et al, 2001;Salat et al, 1999), and a subclinical accumulation of neuritic plaques and neurofibrillary tangles in medial temporal lobe brain regions (Green et al, 2000;Hulette et al, 1998). These brain changes are accompanied by age-related declines in information processing speed, executive functions, and efficiency of learning and recall (Corey-Bloom et al, 1996;Desgranges et al, 1998;Grady et al, 1995;Gunning-Dixon & Raz, 2000;Hulette et al, 1998;Mittenberg et al, 1989;Schacter et al, 1996;Ylikoski et al, 1993).…”
Section: Introductionmentioning
confidence: 99%